Protective hood - Abdul Aziz, Abdul Haffiz; Md Sobhi, Muhammad Alif Asyraf; Othman, Siti Amira (Penerbit UTHM, 2020)
Protective hood is intended to give limited protection to head and neck. It is an interface device of a properly selected and configured protective ensemble during fire fighting and related emergency response activities.